Pendampingan Pengembangan Kurikulum Berbasis Moderasi Beragama dan Pemanfaatan Teknologi Informasi Bagi Mts dan MA Al-Muayyad Tegowanu Grobogan : Pengabdian - Slamet Panuntun; Subaidi; Aliwan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of education in madrasahs plays an important role in shaping students’ religious, moderate, and adaptive character in response to contemporary challenges. In the digital era, religious education is required to systematically integrate the values of religious moderation into the curriculum and to be supported by the effective use of information technology. However, limitations in teachers’ competencies remain, particularly in integrating religious moderation values and optimally utilizing information technology in the learning process. This Community Service Program aimed to assist in the development of a curriculum based on religious moderation and to enhance teachers’ competencies in the use of information technology at MTs and MA Al-Muayyad Tegowanu, Grobogan Regency. The method employed was training and mentoring using a participatory approach involving 29 teachers. The results indicate a significant improvement in teachers’ understanding of religious moderation, their ability to design curricula and learning tools integrated with moderation values, and their skills in utilizing information technology. As a result, learning activities became more inclusive, contextual, and engaging for students. This program provides a tangible contribution to strengthening religious moderation and developing technology-based learning in madrasahs and has the potential to be replicated in other Islamic educational institutions.